Information Provision and Streamlined Medical Service: Evidence from a Mobile Appointment App - Changcheng Song; Nan Yang; Junjian Yi; Ye Yuan (Institute of Labor Economics (IZA), 2018)
We examine the launch of a mobile outpatient appointment app in China to study the effect of information provision and a streamlined appointment process on hospital operations and the alignment of healthcare supply and demand. Using a longitudinal dataset on hospital operations and a difference-in-differences model, we document that the app increases completed hospital consultations by 9.5%, through boosting registrations by 4.8% and reducing appointment cancellations by 3.4%. The app improves queuing efficiency in overcrowded hospitals and draws demand for underutilized ones. Supported by additional evidence from a subset of patients' electronic medical records, we also find that the app directs patients to the hospital and department more suitable to their medical conditions and to less busy days, resulting in a better match between patient demand and hospital service.
Keywords: I11; I12; I18; 330; healthcare information technology; information provision; hospital operations; patient sorting; patient choices